2008
DOI: 10.1002/14651858.cd004024.pub2
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with autologous stem cell transplantation in the first line treatment of aggressive Non-Hodgkin Lymphoma (NHL) in adults

Abstract: . Despite higher CR rates, there is no benefit for high-dose chemotherapy with stem cell transplantation as a first line treatment in patients with aggressive NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
11

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 67 publications
3
52
0
11
Order By: Relevance
“…77 Several studies evaluating its role following response to rituximabbased chemotherapy have recently been performed. (Table 1) Preliminary results of a randomized trial comparing R-CHOP-14 vs ASCT in young patients with DLBCL demonstrated no difference in outcome.…”
mentioning
confidence: 99%
“…77 Several studies evaluating its role following response to rituximabbased chemotherapy have recently been performed. (Table 1) Preliminary results of a randomized trial comparing R-CHOP-14 vs ASCT in young patients with DLBCL demonstrated no difference in outcome.…”
mentioning
confidence: 99%
“…For these aforementioned reasons, multiple sensitivity analyses were performed, and these analyses confirmed the conclusions regarding an overall [Gisselbrecht et al 2002;Greb et al 2008]. This trial was chosen for exclusion due to its exceptionally poor outcomes in patients with IPI high-risk disease receiving ASCT.…”
Section: Role Of Consolidative Asct In Dlbcl Following Induction Chemmentioning
confidence: 78%
“…The most comprehensive and recent meta-analysis of the clinical trials data regarding frontline ASCT in patients with DLBCL was authored by Greb and colleagues and published in 2008 in the Cochrane Database of Systematic Reviews [Greb et al 2008]. This meta-analysis drew data from 15 RCTs comparing OS and event-free survival (EFS) in patients with diffuse, aggressive NHL who received either frontline ASCT or chemotherapy alone.…”
Section: Role Of Consolidative Asct In Dlbcl Following Induction Chemmentioning
confidence: 99%
“…[27][28][29] A Cochrane review of the role of upfront HDT/auto-SCT in aggressive NHL concluded that there was no benefit to auto-SCT over chemotherapy, although not all studies reviewed included patients with BL. 30 Prospective studies in selected BL patients have reported only modest outcomes with upfront SCT. It should be noted, however, that these studies were not designed to directly compare chemotherapy with an autograft.…”
Section: Auto-sct In Blmentioning
confidence: 99%